Evaluating Awareness and Practices in Household Wastewater Management in Riverside Dwellers: Implications for Policy and Education - Valera, John Paul R.; Kayvee Mae D. J. Castillo; Mendez, Crystel May B.; Basilio, Eleonor R. (International Journal of Environment, Engineering and Education, 2024)
In rapidly urbanizing regions like Bambang, Bocaue, Bulacan, managing household wastewater has become a pressing challenge, primarily due to rapid population growth and inadequate infrastructure. Effective wastewater management is critical to safeguarding environmental and public health, yet it often remains overlooked in developing areas. This study investigates riverside dwellers' awareness levels and practices regarding household wastewater management, aiming to bridge data gaps and provide valuable insights for policymakers, researchers, and stakeholders. By addressing these issues, the research contributes to a deeper understanding of the current challenges and opportunities for improving wastewater practices in the area. The study employs quantitative methods, including surveys and statistical analyses, to examine the demographic profiles, awareness levels, and wastewater management practices of 111 households. Findings reveal a troubling lack of awareness among respondents regarding proper wastewater management, disposal methods, and their environmental impacts. Most households report directly discharging wastewater into nearby water bodies, with only minimal use of appropriate treatment facilities. This practice poses substantial risks, including water pollution, ecosystem degradation, and threats to community health, particularly in a densely populated and ecologically sensitive area like Bambang. These findings underscore the urgent need for targeted interventions to address this critical issue. Community education programs are essential to raise awareness of wastewater management's importance and environmental impacts. Simultaneously, infrastructure investments—such as constructing affordable and accessible treatment facilities—are crucial for enabling proper wastewater handling. The study also emphasizes the necessity for robust policy measures, including stricter regulations and enforcement, to ensure sustainable wastewater management practices.